Epidemiology of Premature Ejaculation and its Impact on Quality of Life - Quek Kia Fatt (Public Health, 2017)
Premature ejaculation (PE) is one of the major sexual problem among men. The prevalence varies worldwide ranging from 4 to 66% according to various studies. The aetiology and pathophysiology of PE are still poorly understood. The associated risk factors for PE varies from folate deficiency, metabolic syndrome/diabetes, neurobiological and genetic factors/ge-netic predisposition, neurological disorders, recreational drugs and alcohol, chronic prostatitis/chronic pelvic pain syndrome, thyroid disorder, emotional problem/depression/stress/anxiety, history of traumatic sexual experiences/conditioning, erectile dysfunction (ED), low sexual in-tercourse frequency. PE has a great impact on the men’s quality of life (QoL) where it can lead to embarrassment, frustration, feeling of incompetence, depression and sexual dissatisfaction. The management of PE varies from non-pharmacological therapy including counselling; and pharmacological therapy. PE does not just affect the man but also his female partner. As such, it is important that women understand the issue and provide adequate moral support to the male partner to address the issue together.